Study protocol for COVID-19 breakthrough infections and vaccine-induced immune response among a cohort of healthcare workers, Bangladesh. - Md Zakiul Hassan; Ahamed Khairul Basher; Mohammed Ziaur Rahman; Taufiqur Rahman Bhuiyan; Fahmida Chowdhury; Md Kamal Hossain; Aninda Rahman; Md Nazmul Islam; Lindsey M Duca; Susan Cornelia Kaydos-Daniels; Benjamin A Dahl; Firdausi Qadri; et al. (PLoS ONE)
Background To optimize vaccination strategies, it is useful to detect breakthrough infections and assess vaccine effectiveness in programmatic use. Monitoring emerging SARS-CoV-2 variants and vaccine effectiveness against them is also essential to determine the most effective vaccine options. This study aims to monitor SARS-CoV-2 breakthrough infections, the emergence of new SARS-CoV-2 variants, and host immune response during the peri-infection period of COVID-19. The study will also assess the uptake of the COVID-19 vaccine booster doses, and associated barriers or motivations among healthcare workers (HCWs). Methods Leveraging an existing HCW cohort in Bangladesh, HCWs will be enrolled from purposively selected health facilities from four different administrative divisions across Bangladesh. We captured cohort data on HCW's demographic information, clinical information, COVID-19 illness, and exposure, and vaccination histories for COVID-19. However, no biological specimens were collected for testing during the first phase of the cohort. In the current study, we plan to follow enrolled HCWs biweekly for suspected COVID-19 illness and capture relevant data including illness outcomes. Respiratory swab samples from symptomatic and a subset of asymptomatic HCWs will be tested for SARS-CoV-2 by rRT-PCR and positive samples will undergo Sanger sequencing to identify the SARS-CoV-2 variants of concern (VOCs). We will also perform Whole Genome Sequencing on a subset of SARS-CoV-2 positive samples with low CT values (Ct ≤ 30) to identify emerging SARS-CoV-2 variants. To examine the antibody response, we will collect blood samples from the participants at 12-week intervals for one year. We will use the EUROIMMUN kit and will also perform in-house ELISA to assess host immune factors with Luminex platform. Discussion This proposed study will generate useful data on COVID-19 breakthrough infection and the durability of anti-SARS-CoV-2 antibodies among HCWs following vaccination. The findings on booster vaccination intention and uptake will inform government COVID-19 vaccination strategies. Information on circulating and emerging strains of SARS-CoV-2 and vaccine performance against those strains will help understand population-level risks of COVID-19 infection. The study will generate data on facilitators and barriers to COVID-19 booster uptake among HCWs which can inform health communication messaging to improve booster acceptance in this population.